Thermal imaging in biomedical research: a non-invasive technology for animal models - Verduzco-Mendoza, Antonio; Olmos-Hernández, Adriana; Bueno-Nava, Antonio; Villanueva-García, Dina; Domínguez-Oliva, Adriana; Avila-Luna, Alberto; Mora-Medina, Patricia; Gálvez-Rosas, Arturo; Hernández-Ávalos, Ismael; Casas-Alvarado, Alejandro; Garnica, Marco A.; Mota-Rojas, Daniel (Frontiers in Veterinary Science, 2025)
Thermal imaging has been used in animal models to non-invasively detect surface temperature changes after several pathologic and surgical processes. Infrared thermography (IRT) identifies increases or decreases in radiated heat according to blood circulation and microcirculation. The present review aims to discuss the most relevant aspects of IRT applied in biomedical research as a noninvasive technique in animal models, highlighting its importance in a clinical setting and for translational medicine. IRT provides an alternative to evaluate vascular anomalies where blood flow is interrupted. In surgical processes such as anastomosis and reconstructive techniques (e.g., grafts and flaps), thermal imaging can assess the viability of tissues. In burn injuries, IRT can predict and identify the areas of ischemia-necrosis and inflammation. Nonetheless, although IRT is a potential alternative to use in both animal models and human patients, the use of IRT and other imaging techniques is encouraged.